2017
DOI: 10.3389/fmars.2017.00288
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of Maps and Models in Conservation and Resource Management (Warning: Results May Vary)

Abstract: Conservation planning and management typically require accurate and spatially explicit data at scales that are relevant for conservation objectives. In marine conservation, these data are often combined with spatial analytical techniques to produce marine habitat maps. While marine habitat mapping is increasingly used to inform conservation efforts, this field is still relatively young and its methods are rapidly evolving. Because conservation efforts do not always specify standards or guidelines for the produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 214 publications
1
35
0
Order By: Relevance
“…This study demonstrated the necessity of assessing benthic environments at a scale relevant to management by uncovering the full breadth of seabed features and associated community diversity, as well as providing a more accurate description of the ‘representativity’ of the MPA. It also emphasizes the need for better ocean floor maps, and the collection of high‐resolution multibeam echosounder data to facilitate marine spatial management, in line with previous recommendations (Brown et al, , ; Cogan et al, ; Lecours, ; Pickrill & Todd, ).…”
Section: Discussionsupporting
confidence: 62%
“…This study demonstrated the necessity of assessing benthic environments at a scale relevant to management by uncovering the full breadth of seabed features and associated community diversity, as well as providing a more accurate description of the ‘representativity’ of the MPA. It also emphasizes the need for better ocean floor maps, and the collection of high‐resolution multibeam echosounder data to facilitate marine spatial management, in line with previous recommendations (Brown et al, , ; Cogan et al, ; Lecours, ; Pickrill & Todd, ).…”
Section: Discussionsupporting
confidence: 62%
“…Species distribution models (SDMs) encompass a suite of tools used to predict the distribution of a species based on specieshabitat relationships, and resulting maps of predicted estimates are widely used to guide protected areas planning and monitor effectiveness to achieve conservation targets (Sanderson et al 2002, Elith and Leathwick 2009, Franklin 2009, Veloz et al 2015, Lecours 2017.…”
Section: Modeling Species Associated With Wet Forest Habitatsmentioning
confidence: 99%
“…Predictive species distribution models (Guisan & Zimmermann, 2000), SDMs, have emerged as powerful tools to identify important habitats for species and for use in biodiversity conservation (Gregr, Baumgartner, Laidre, & Palacios, 2013;Guisan et al, 2013;Lecours, 2017). SDMs can provide important ecological insights into speciesenvironment relationships (Bräger, Harraway, & Manly, 2003;Redfern et al, 2006), enable comparisons among species (Ingram, Walshe, Johnston, & Rogan, 2007;Mannocci et al, 2014;Redfern et al, 2013), identify key areas and habitats (Esteban et al, 2014;Pérez-Jorge et al, 2015), and help predict where species might be most at risk from anthropogenic activities (Ashe, Noren, & Williams, 2010;Redfern et al, 2013).…”
Section: Introductionmentioning
confidence: 99%